Experimental and numerical studies on the buckling and post-buckling behavior of single blade-stiffened CFRP panels. (15th July 2018) - Kolanu, Naresh Reddy; Raju, Gangadharan; Ramji, M.
Abstract: The aim of this study is to experimentally investigate the stability behavior and failure characteristics of carbon fibre reinforced polymer (CFRP) composite panels with secondary bonded blade stiffener under compression. Various experimental techniques like 3D-digital image correlation (DIC), acoustic emission (AE), strain gaging and infrared thermography were employed together for capturing the buckling, post-buckling response and failure characteristics of test panels. The 3D-DIC technique was employed for determining the buckling and post-buckling displacement fields of the test panel. The strain gage data was used for accurate prediction of the onset of buckling phenomenon of the test panels. Parametric data obtained from the AE technique was analysed for identifying and classifying the various damage events encountered in the test panel. In addition, finite element simulation of the CFRP stiffened panel under compression was performed to validate the experimental post-buckling results. In this work, Hashin's failure criteria was used to study the initiation of various failure modes in the critical regions of the stiffened panel. The proposed unified experimental approach can provide more insights on the post-buckling behavior and failure characteristics of single blade stiffened CFRP panels, thereby helping engineers in designing damage tolerant composite structures.